2015
DOI: 10.9744/jmk.17.1.11-20
|View full text |Cite
|
Sign up to set email alerts
|

Relational Benefit, Kepuasan, Dan Loyalitas Pelanggan Pada Bengkel Pt Honda Dewata Motor

Abstract: AbstrakMemberikan kepuasan secara konsisten kepada pelanggan dapat membuat pelanggan menjadi loyal kepada perusahaan. Sikap loyal pelanggan kepada perusahaan akan sangat membantu perusahaan untuk dapat bertahan dalam persaingan bisnis karena pelanggan merupakan sumber pendapatan dari perusahaan. Relationship marketing adalah salah satu strategi pemasaran yang bisa digunakan untuk mencapai tujuan tersebut. Melalui strategi relational benefits, perusahaan dapat memberikan manfaat atas hubungan antara perusahaan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
1
5
0
2
Order By: Relevance
“…The higher customer satisfaction after using Lion Air airline services, the higher the consumer's desire to be loyal or become loyal Lion Air customers. These results are in line with research conducted by Prayoga et al (2015), Putra et al (2018), IRJMIS ISSN: 2395-7492  Devi, A. A. D. T., & Yasa, N. N. K. (2021)…”
Section: The Effect Of Satisfaction On Brand Loyaltysupporting
confidence: 92%
See 1 more Smart Citation
“…The higher customer satisfaction after using Lion Air airline services, the higher the consumer's desire to be loyal or become loyal Lion Air customers. These results are in line with research conducted by Prayoga et al (2015), Putra et al (2018), IRJMIS ISSN: 2395-7492  Devi, A. A. D. T., & Yasa, N. N. K. (2021)…”
Section: The Effect Of Satisfaction On Brand Loyaltysupporting
confidence: 92%
“…Customers can be considered satisfied if the purchase made by consumers for a product given by the company exceeds their expectations. Research conducted by Leong et al (2015), Prayoga et al (2015), Saraswita & Yasa (2017), Famiyeh (2018), Budiarta & Fachira (2017), Pratiwi et al (2019), Atmaja & Yasa (2020), Diputra & Yasa (2021), found a positive and significant influence between consumer satisfaction on brand loyalty. Based on the research results that have been described, the following hypothesis can be formulated: H5: Satisfaction has a positive and significant effect on brand loyalty…”
Section: The Effect Of Perceived Value On Customer Satisfactionmentioning
confidence: 97%
“…Martini (2013), in his research, proves that customer satisfaction positively affects customer loyalty. Byramjee et al (2010), andPrayoga et al (2015), stated that customer satisfaction has a positive influence on increasing consumer loyalty. RANI (2016), proves that there is a positive effect of customer satisfaction in increasing customer loyalty.…”
Section: Introductionmentioning
confidence: 99%
“…The research results conducted by Prayoga et al(2015) stated that confidence has a positive and significant effect on customer satisfaction. The use of mobile banking on smartphones has the benefit of making it easier for customers to meet their financial needs and is directly related to customer satisfaction (Tran and Corner 2016).…”
Section: Relationship Between Benefit Offered and Satisfactionmentioning
confidence: 98%